Parallel firing strategy on petri nets: a review - Mavlankulov, Gairatzhan; Turaev, Sherzod; Zhumabaeva, Laula; Zhukabayeva, Tamara (American Institute of Physics, 2015)
In this paper we review the recent results related on Petri net controlled grammars and the close related topics. Though the theme of regulated grammars is one of the classic topics in formal language theory, a Petri net controlled grammar is still interesting subject for the investigation for many reasons. This type of grammars can successfully be used in modeling new problems emerging in manufacturing systems, systems biology and other areas. Moreover, the graphically illustrability, the ability to represent both a grammar and its control in one structure, and the possibility to unify different regulated rewritings make this formalization attractive for the study. We also summarize the obtained results and propose a new conception such as parallel firing strategy on Petri Nets.